Mimotopes of heat shock proteins of Salmonella enterica serovar Typhi identified from phage-displayed peptide library - Yuen, Hawk Leong; Shamala, Devi; Thong, Kwai Lin (Open Learning on Enteric Pathogens, 2008)
BACKGROUND: Heat shock proteins (HSPs) are known to be involved in the pathogenesis of Salmonella enterica serovar Typhi (S. Typhi), the causative agent of typhoid fever. The objective of this study was to apply a phage display library to identify mimotopes of two HSPs, HSP90 and DnaK in S. Typhi.